2020
DOI: 10.1002/hbm.25298
|View full text |Cite
|
Sign up to set email alerts
|

Musical instrument training program improves verbal memory and neural efficiency in novice older adults

Abstract: Previous studies indicate that musical instrument training may improve the cognitive function of older adults. However, little is known about the neural origins of training‐related improvement in cognitive function. Here, we assessed the effects of instrumental training program on cognitive functions and neural efficiency in musically naïve older adults (61–85 years old). Participants were assigned to either the intervention group, which received a 4‐month instrumental training program using keyboard harmonica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 85 publications
0
28
1
Order By: Relevance
“…While research on music-based interventions for motor rehabilitation of older adults is scarce, there is growing evidence of the effectiveness of short-term musical training for cognitive rehabilitation in this population ( Bugos et al, 2007 ; Seinfeld et al, 2013 ; Bugos, 2019 ; MacRitchie et al, 2020 ). Although a thorough review of the effectiveness of music-based intervention in cognitive rehabilitation is beyond the scope of this paper (for further discussion, see Hegde, 2014 ; Sihvonen et al, 2017 ; Fusar-Poli et al, 2018 ; Koshimori and Thaut, 2019 ; Schneider et al, 2019 ; Mollica et al, 2021 ), it is of note that recent intervention studies have shown significant improvements in cognitive function in healthy older adults involved in piano training programs ( Bugos and Kochar, 2017 ; Degé and Kerkovius, 2018 ; Bugos, 2019 ; Zendel et al, 2019 ; MacRitchie et al, 2020 ; Guo et al, 2021 ; Worschech et al, 2021 ). For instance, in MacRitchie et al (2020) , 15 older adults (aged 65 years or older) participated in a piano training program consisting of ten 60-min group lessons involving learning to play simple melodies and ensemble playing tasks.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…While research on music-based interventions for motor rehabilitation of older adults is scarce, there is growing evidence of the effectiveness of short-term musical training for cognitive rehabilitation in this population ( Bugos et al, 2007 ; Seinfeld et al, 2013 ; Bugos, 2019 ; MacRitchie et al, 2020 ). Although a thorough review of the effectiveness of music-based intervention in cognitive rehabilitation is beyond the scope of this paper (for further discussion, see Hegde, 2014 ; Sihvonen et al, 2017 ; Fusar-Poli et al, 2018 ; Koshimori and Thaut, 2019 ; Schneider et al, 2019 ; Mollica et al, 2021 ), it is of note that recent intervention studies have shown significant improvements in cognitive function in healthy older adults involved in piano training programs ( Bugos and Kochar, 2017 ; Degé and Kerkovius, 2018 ; Bugos, 2019 ; Zendel et al, 2019 ; MacRitchie et al, 2020 ; Guo et al, 2021 ; Worschech et al, 2021 ). For instance, in MacRitchie et al (2020) , 15 older adults (aged 65 years or older) participated in a piano training program consisting of ten 60-min group lessons involving learning to play simple melodies and ensemble playing tasks.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Because these studies showed within-nonmusicians differences in levels of load of executive function for different complexity of tapping, the relationship between the previous findings and our between-groups difference cannot be clearly interpreted. Since musical performance requires motor planning and monitoring of finger movement (Palmer and Drake, 1997;Moreno et al, 2011;Shen et al, 2019;Colombo et al, 2020;Guo et al, 2021), we suggest that musicians perform finger taps with higher executive involvement compared to non-musicians even when they are simple ones. The higher levels of executive function in musicians can be maintained by the same processes to enable masterful temporal and ordinal precision of finger movements, together with fine-grained finger force control.…”
Section: The Effect Of Lifelong Musical Training: From Skillful Tapping To Cognitionmentioning
confidence: 94%
“…Cognitive tests consisted of the Japanese versions of parts A and B of the trail-making test (TMT; Reitan and Wolfson, 1993 ) and logical memory-I and -II subtests of the Wechsler Memory Scale-Revised edition (WMS-R; Wechsler, 1997 ; Sugishita, 2000 ). Motor tests consisted of timed up and go (TUG; Podsiadlo and Richardson, 1991 ) and pegboard (Guo et al, 2020 ) tasks.…”
Section: Methodsmentioning
confidence: 99%
“…Next, the associations between sports traits and the GMVs in the ROIs were investigated. Based on the structural result differences between the groups, we used MarsBaR software (Brett et al, 2002 ) to extract spherical ROIs that centered on the local maximal peaks of the significant clusters (we used sub-clusters for overly large clusters) that were located within a 10-mm radius of the regions identified in the aforementioned analysis (Guo et al, 2020 ). Correlation analyses were conducted using the Pearson’s correlation coefficient.…”
Section: Methodsmentioning
confidence: 99%